Autoconcepto y representaciones sociales de brasileños sobre sus experiencias LGBTQIA+ - de Sousa Barros Neto, Raimundo Nonato (Universidad de Costa Rica, 2024)
Objective. The objective of this research was to identify the constituent elements of the self-concept and the representational structure of Brazilians about their LGBTQIA+ experiences Method. The study involved the participation of 120 LGBTQIA+ people, all Brazilian, aged between 18 and 42 years (M = 27.19 and SD = 5.95). Data collection employed a sociodemographic questionnaire and the Free Word Association Test (FWAT) with the inducing stimulus "Myself". Results. The analysis indicated that participants demonstrated positive self-representations, suggesting a healthy self-concept. However, despite the predominance of positive traits, the stressors faced by LGBTQIA+ individuals may negatively impact their self-concept. In this context, some of the words evoked following the presentation of the inducing stimulus referred to negative characteristics and feelings associated with an impoverished self-concept.